Phonological Exploitation in Constructing Humourous Utterances - Imam Romadlani; Eka Susylowati; Meria Alfisuma (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
This research is conducted to reveal the strategy of humour construction dealing with phonological exploitation in Mind Your Language situation comedy. Mind Your Language is a British comedy television series that portrays a learning process by immigrants coming from various countries. Varieties of cultures and levels of English knowledge naturally influence humour creation by the characters. The data were taken from humourous utterances in season one of that situation comedy. Applying a descriptive qualitative approach, this research is in an attempt to find out the forms and the motives of those humourous utterances created to entertain audiences, especially those dealing with phonological aspects. The findings demonstrate that six forms of phonological aspects are employed to create humour. Sounds addition, omission, substitution, and minimal pairs are frequently exploited in humour creation rather than other strategies such as sound compatibility and metathesis. Based on the motives of humour construction, besides the interlocuter’s influence, the phonological interference phenomenon also grounds the humour production in Mind Your Language situation comedy. The humourous utterances produced illustrate a contextual relation of the situation comedy as an English learning process by immigrants coming from various countries, languages, and cultures.